1972
DOI: 10.1159/000266221
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Conjugation of Cortisol in the Lens

Abstract: Sulphate and glucuronide conjugation of cortisol in the normal human, cataractous, bovine, rabbit and rat lens in vitro have been investigated using a cortisol-4–14C. The authors have verified the presence of sulphate and glucuronide conjugation of cortisol in the lens. There are species differences in conjugation of steroid in the lens. Conjugation in the human lens was found to be more active than that in other animals. Sulphate conjugation of cortisol in the cataractous lens was less than that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1973
1973
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Riboflavin undergoes complex photochemical reactions with proteins in vivo. Photolysis of RB in the lens of the eye leads to the formation of flavin-ocular protein adducts. , Photolysis of RB in plasma (which transpires when jaundiced newborns are treated for hyperbilirubinemia) produces a flavin-albumin adduct. The structures of these adducts are not known, but it has been determined that tryptophan residues are involved in this linkage . It seems likely that adduct formation involves the triplet state of the flavin because adduct formation is quenched by 10 mM ascorbate ion …”
Section: Introductionmentioning
confidence: 99%
“…Riboflavin undergoes complex photochemical reactions with proteins in vivo. Photolysis of RB in the lens of the eye leads to the formation of flavin-ocular protein adducts. , Photolysis of RB in plasma (which transpires when jaundiced newborns are treated for hyperbilirubinemia) produces a flavin-albumin adduct. The structures of these adducts are not known, but it has been determined that tryptophan residues are involved in this linkage . It seems likely that adduct formation involves the triplet state of the flavin because adduct formation is quenched by 10 mM ascorbate ion …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the liver is the organ primarily responsible for the catabolism of the steroid hormone (19). It may be thought that changes in the liver function could either directly or indirectly influence the steroid hormone metabolism in the lens as reported previously (20), and finally it would bring about a reduction in the synthesis of cortisol-binding protein in the lens.…”
Section: Discussionmentioning
confidence: 79%
“…We have demonstrated that cortisol binding by lens protein is carried out fairly actively leading to inactivation of steroid hormone in the lens (1).…”
mentioning
confidence: 92%
See 1 more Smart Citation